The future of the students of the College of Basic Education (Journal of the College of Basic Education, 2022)
The issue of youth is one of the main topics that receive the attention of psychologists, education, sociologists, politicians and others, because youth are one of the most important social segments, and they constitute the basic element in the human factor that all countries adopt in the development and progress of society.University students constitute the most important component of the youth segment, as they are the educated class among the youth, and upon it rests the responsibility for building, change and progress. University education has become a field for many studies and researches that have focused on youth problems and issues.Among the most common problems facing students at the present time, and whose effects may be severe in the future, are academic, family, social, health, personal, and other problems. These problems vary according to individuals and their circumstances.Increasing the burdens and difficulties faced by university students would increase their fear and apprehension about the future, in addition to the increase in the pressures they might be exposed to would also increase their anxiety in general and the future in particular.Future anxiety is associated with many psychological, social and economic factors and the conditions of rapid change that society is going through, and the expectation of the threat that arises from future anxiety is closely related to the psychological factors of the individual, and perhaps the feeling of psychological loneliness is one of the psychological factors or variables that future anxiety is associated with and that would Increasing the feeling of this anxiety and the burdens and pressures it adds, its effects and negative consequences appear on the various aspects of the personality, in addition to the negative effects and results of future anxiety and psychological loneliness that may be negatively reflected on the psychological and social compatibility and the level of mental health of university students. Consequently, it may affect their motivation, skills, scientific and professional abilities, and disrupt their energies and creativity.